Does Digital Transformation Drive Economic Growth? Evidence From Asian And European Countries - Saeed A.A. Saif (DAS Institute, 2026)
This study investigates the impact of digital transformation on economic growth using panel data from selected Asian and European countries. It examines how key digitalization indicators shape differences in economic performance across regions with distinct structural and developmental characteristics. The analysis employs a fixed-effects panel model to control for unobserved country-specific heterogeneity. Descriptive statistics, correlation analysis, and robustness tests using Driscoll–Kraay standard errors are applied to address heteroscedasticity, autocorrelation, and cross-sectional dependence. Economic growth is measured by GDP per capita. Digital transformation is captured through internet usage, mobile subscriptions, ICT service exports, and high-technology exports. The model also includes control variables for infrastructure availability and trade openness. The results show that digital transformation significantly supports economic growth, although its effects vary across regions. Internet penetration, mobile connectivity, and ICT service exports have positive and statistically significant effects on GDP per capita, particularly in Asian economies. In contrast, high-technology exports are negatively associated with growth, indicating possible structural limitations and adjustment costs in technology-intensive sectors. The regional analysis suggests that Asian countries benefit more from expanding basic digital infrastructure, while European economies gain more from advanced ICT services. Overall, the findings provide comparative regional evidence on the digital transformation–growth nexus and emphasize the importance of context-specific digital development strategies.